Efektifitas Penyelesaian Sengketa Ekonomi Syariah Pendekatan Mediasi Dalam Perspektif Yuridis Normatif - Fauzi, Muhammad; Siswoyo; Yani, Ahmad; Elsa Ilka Sasena; Nasri, Halik; Ongky Alexander (Hutanasyah : Jurnal Hukum Tata Negara, 2025)
Dispute resolution in sharia economics often poses its own challenges, especially when the litigation path is considered slow, expensive, and does not reflect the values ??of justice and peace that are the main foundations of sharia principles. In this context, mediation emerges as an alternative resolution that offers efficiency, flexibility, and a more humanistic approach. Based on literature review, mediation has been proven to have a strong legal basis, both in Islamic legal sources such as the Qur'an and hadith, as well as in national regulations, including the Supreme Court Regulation and the Religious Courts Law. A number of literatures show that mediation not only accelerates the dispute resolution process and reduces the burden on the courts, but also maintains good relations between the disputing parties, which is very important in the sharia business world. In practice, mediation provides a higher level of satisfaction than litigation because it allows for a fair agreement to be reached by consensus. Therefore, mediation can be concluded as an effective dispute resolution approach that is in line with the values ??of sharia economics and contemporary legal needs in Indonesia.